Feedforward control of nonlinear systems using fictitious inputs - Deutscher, Joachim; Schmidt, Klaus; Antritter, Felix (44th IEEE Conference on Decision and Control, and the European Control Conference, CDC-ECC '05, 2005)
This paper presents the differential parameterization of nonlinear systems using a parameterizing output with differentially dependent elements, that results from introducing fictitious inputs in the original system description. The proposed differential parameterization is used to design feedforward controllers for output tracking. The results of the paper are illustrated by a non-flat helicopter model and a three-phase ac/dc voltage-source converter with unstable tracking dynamics. © 2005 IEE